Changing perceptions on menstrual practices in Southern Bangladesh: a cross-generational study - Jeni, Jannatul Bakia; Shindaini, Al Jamal Mustafa; Mahtab, Md. Tanvir; Saha, Shantanu Kumar (Intelektual Pustaka Media Utama, 2025)
Menstruation, a natural biological process, remains deeply intertwined with women's lives but is surrounded by superstitions and stigmas, posing health risks. This study explores generational shifts in menstrual perceptions, focusing on women's knowledge, rituals, social stigmas, and the evolving sources of socialization. Using a phenomenological approach, interviews were conducted with women from 25 households, spanning three generations. Thematic analysis has been used to analyze the data. Findings revealed that while the first and second generations understood menstruation primarily as a sign of fertility and bodily maturity, the third generation recognized it as a hormonal process. Hygiene practices also varied, with older generations relying on cloths and holy water for pain relief, whereas younger women opted for sanitary pads and were more aware of the dangers of unhygienic practices. Additionally, the study highlighted prevalent misconceptions and stigmas among the first and second generations, while the third generation was more informed, open, and vocal about menstruation. The process of socialization around menstruation has also evolved; earlier generations mainly learned from their mothers, with little involvement from male family members. In contrast, the third generation gained knowledge from both parents and media, reflecting a significant shift in the cultural dialogue surrounding menstruation.